(3EOGQI GdEFJeGf GdeUQaj hJMdjd GdEFJeGfjs - (3MeRI eMehO(B, (3GdRHjOjs ((3YeGf(B:s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B,s, 2002)
(3GdEFJeGf GdeUQaj, eGgjJg hCgejJg(B- (3JfXje GdEFJeGf GdeUQaj hGdQbGHI Ydjg(B-(3CfhGY GdEFJeGf GdeUQaj(B- (3GdESJYdGe hGdJMbb aj EOGQI GdEFJeGf(B- (3eYGjjQ efM GdEFJeGf(B- (3JMdjd eNGWQ GdEFJeGf(B- (3bhGYO efM GdEFJeGf(B- (3GdJMdjd GdEfJeGFj GdfhYj hGdafj(B- (3GdJMdjd GdEFJeGfj dJLfH eNGWQ GdaTd GdeGdj(B- (3EOGQI GdEFJeGf hEMJjGLGJ GdYejd hGdfeh GdbGHd ddESJeQGQs
Keywords: (3GdEFJeGf GdeUQajs; (3GdEOGQI GdeGdjIs; (3GdbQhV GdHfcjIs